Research on Locomotion Characteristics of a Novel Hopping Robot - Wang Jian; Zhang Wenxiang; Miao Long; Wang Shukun (Jixie chuandong)
One legged mechanism model of a novel hopping robot is presented. The kinematics equations during stance and flight phases are established and its direct and inverse kinematics characteristics are studied by the D-H method. The expression about the hopped position is given. Dynamic characteristics of the hopping robot are analyzed by Adams software. The simulation results confirm that the horizontal/vertical displacement curves and horizontal/vertical velocity curves are consistent with the experimental ones. The research shows the feasibility of this hopping model and validity of the research method.